Urinary Tract Infections During Early Posttransplant Period in Adult kidney Allograft Recipients - Islam, MD Nazrul; Dutta, Pradip Kumar; Akhter, Mursheda; Das Gupta, Ratan; Uddin Joardder, MD Sahab; Salehuddin, Firoz; Rahman, MD Mustafizur; Rashid, Harun UR (Journal of Medicine, 2011)
Background: Urinary tract infections (UTIs) represent the most common cause of bacterial infection in renal allograft recipients. The purpose of this study was to evaluate UTI in renal transplant recipients at earlier post transplant period (first 3 months) and isolation of causative organism. Materials & methods: We studied 31 patients (18 males and 13 females), aged 27 ± 8.8 years. UTIs occurring during the first three months were analyzed. During this period, all episodes of infection, transplant function, graft survival and patient survival were monitored. Results: Twenty two patients had suffered from different types of infection within first 3 months of transplantation, most of the infectious episodes occurred during hospital stay. Most of the infection occurred in urinary tract and most of the episodes of UTI were asymptomatic, presented with bacteriuria. Most of the isolated organisms were Gram negative E.Coli. Out of 51 episodes of bacterial infection, UTIs account for 49 episodes (96%) Patients’ age, sex and acute rejection episodes did not correlate with UTI. Patient who had prolonged urethral catheterization had suffered from significantly more number of UTI in comparison to short period of urethral catheterization (p=0.02).Similar incidence of UTI were observed in ureteric stented and non stented patients but non stented patients had suffered from significant number of urological complication (p<0.02) . Antibiotic sensitivity pattern revealed that, all isolates were sensitive to ciprofloxacin, ceftriaxone and ceftazidime, ranged between, 67 to 100% and highly resistant to ampicillin, cotrimoxazole and cephradine. Conclusion : Short term renal graft function was not found to be affected by UTI occurrence. UTIs are common infectious complications in renal transplant recipients and often relapse and require hospitalization. Keyword: urinary tract infections (UTIs), renal transplantation, acute rejection episodes. DOI: http://dx.doi.org/10.3329/jom.v12i2.8416 JOM 2011; 12(2): 103-108